Children with disabilities in child and family welfare services. (21st May 2014) - Mitchell, Gaye
<x content-type="archive" xml:space="preserve">Abstract</x> There is a lack of research data about children with disabilities across the range of child and family welfare services. The study reported in this paper explored the extent and nature of disabilities in children in a variety of programmes within OzChild, an Australian welfare agency. Caseworkers and teachers working with children at the beginning of 2012 considered all children receiving services from their programmes. Of these 475 children, 200 were identified as having a disability. This article presents data on these 200 children and recommendations for improving outcomes for them. A major finding was that disability added further layers of complexity to already complex child–carer/family situations presenting to under-resourced practitioners and programmes. There was an extensive variety of disabilities across all programme areas, and varying proportions across programmes ranging from 29 per cent in kinship care and family services to 44 per cent of children in foster care. Data were suggestive of problems with some diagnoses, and the need for further research in these areas. The need to address questions of causation of environmentally based disability through preventative programmes, and a more targeted approach to families with multiple and complex needs were indicated. Lack of respite care was jeopardising some placements of children with severe disability. Lack of educational achievement and participation in social, cultural and recreational activities were identified, as were inequities in funding across different programme areas – all of which resulted in some children with disabilities continuing to be substantially disadvantaged. These data led to the generation of recommendations for changes to practice, programme and policy to improve outcomes for children.